2011
DOI: 10.2174/138527211796150561
|View full text |Cite
|
Sign up to set email alerts
|

The Meyers Reaction (1994-2010)

Abstract: The Meyers reaction, i.e. the nucleophilic aromatic substitution reaction between aryloxazolines with organolithium and organomagnesium reagents is a very efficient and reliable method for the formation of new carbon-carbon and carbon-heteroatom bonds. The aim of this review is to present a general overview of this reaction in chiral and racemic form, emphasizing its scope and limitations. The literature is covered since 1994.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…It was revealed that the reaction did not proceed in the absence of chromium­(II) chloride (Table , entry 1). This result suggests that a nucleophilic aromatic substitution with Grignard reagent involving a Meyers-type reaction mechanism can be excluded in the transformation . CrCl 3 displays high reactivity in the promotion of the C–O bond-activation/cross-coupling reaction (entry 3).…”
Section: Resultsmentioning
confidence: 95%
“…It was revealed that the reaction did not proceed in the absence of chromium­(II) chloride (Table , entry 1). This result suggests that a nucleophilic aromatic substitution with Grignard reagent involving a Meyers-type reaction mechanism can be excluded in the transformation . CrCl 3 displays high reactivity in the promotion of the C–O bond-activation/cross-coupling reaction (entry 3).…”
Section: Resultsmentioning
confidence: 95%
“…The transition-metal-free coupling reaction of organic halides with Grignard reagents is a formidable challenge in the organic synthesis . In addition, a survey of the literature revealed that there were only a few reports on the coupling reaction of organic fluoride with Grignard reagents under transition-metal-free conditions. , However, successful examples of these coupling reactions are limited to substrates containing directing groups. , Encouraged by the above success, we next examined the feasibility of tertiary butylation of gem -difluoroalkene under transition-metal-free conditions. Only a trace amount of Z - 3aa was observed when the reaction was performed in THF without the addition of CuCN at rt (entry 14).…”
mentioning
confidence: 73%
“…These most commonly involve fluorobenzenes substituted with a variety of activating groups, including nitro, cyano, sulfonyl, sulfinyl, bromide, keto, or ester, 8 the mechanisms of which have been characterised both kinetically 9 and theoretically. 10 However, when fluoro and alkoxy groups are on naphthoic acids, carboxyl groups (CO 2 H) usually require protection and subsequent deprotection steps, 11 in processes where they are converted into an oxazoline, 12 a bulky ester, 13 or an imino group. 14 In these systems, alkyl and aryl substitution can now be readily accomplished in generally excellent yields in the absence of a metal catalyst via a nucleophilic displacement of an ortho-fluoro or methoxy group in unprotected naphthoic acids with lithium ion and Grignard reagents.…”
Section: Introductionmentioning
confidence: 99%